Parents' perceptions of the long-term appropriateness of a psychosocial intervention for children with attention deficit hyperactivity disorder - Allan, N.; Wilkes-Gillan, S.; Bundy, A.; Cordier, Reinie; Volkert, A. (Wiley-Blackwell Publishing Asia, 2018)
Background/aim: Designing psychosocial interventions that parents perceive as appropriate is essential to enhancing their engagement with the intervention and their long-term use of the intervention strategies. The aim of this study was to explore the long-term appropriateness of a play-based psychosocial intervention for children with Attention Deficit Hyperactivity Disorder (ADHD) from the perspectives of parents. Methods: Semi-structured phone interviews were conducted with 14 parents of children with ADHD who participated in a randomised controlled trial of the play-based intervention 1 year earlier. Results: Thematic analysis led to the development of three core-themes: (i) Everybody needs a parenting handbook, (ii) No one thing you are dealing with, and (iii) A different approach: Reframing. Discussion: The core-themes related back to a definition of intervention appropriateness that acknowledges the intervention as important/relevant, beneficial, socially and ecologically valid and promotes sustainable change, indicating parents perceived the intervention as appropriate. The core-themes also resembled aspects of the process of family adaptation. Findings highlight the importance of designing interventions that are appropriate from parents' perspectives to enhance their long-term engagement and use of the intervention strategies as well as outcomes for their child in the long term. Australian Occupational Therapy Journal